SENTIMENT ANALYSIS OF CONVERSATION AND RADICAL VIEW NETWORKS ON TWITTER USING SUPERVISED MACHINE LEARNING - Taufiqorrahman Arsyam, Ariq
The background of this research is the phenomenon of self-radicalization which is internet mediated. in this way people can go through the entire radicalization process from candidates to carrying out terrorist operations. The narrative on radicalism becomes the end of the initial amplification of the action. This narrative can be threatening when acquired by people with identity crisis. Aforesaid narrative, if it is poorly controlled, can be dangerous for sustainability of nationality, even more dangerous than the terrorism itself. This research attempts to analyze the sentiment of the radicalism discourse phenomena as an organized, integrated, systematic, and sustainable process carried out by the accounts that are related to the radicalism issue in the form of Twitter post (tweet). This research also wants to describe the form of the Social Network Analysis (SNA) network, the role and involvement of the Twitter accounts related to radicalism to cut the communication lines and the amplification intensity of their ideas. We categorize radicalism discourse on Twitter in the form of sentiment clusters, using the Supervised Machine Learning method with the naïve baiyes algorithm and Nazief & Adriani stemming. We also analyzed the communication network activity, intensity, role and involvement of the Twitter accounts in the radicalism discourse, mapped using SNA by aggregating the Twitter accounts involved in the conversation. The scenario testing has been carried out where the training data and the testing data taken from the 1,060 datasets with the percentage of distributions are 75% for the training data and 25% for the testing data. The testing with this scenario produces the values of confusion matrix accuracy with a confidence level of up to 92%. This is higher than previous studies with SVM, which is only 70% to 83%. The results of the analysis found that rejection of radicalism was represented by negative sentiment (44.46%), a slight difference compared to the positive sentiment (40.91%), representing a group that was skeptical of counter-narrative of radicalism. Meanwhile, neutral sentiment (14.63%) represents the group who are doubtful and apathetic towards the counter-narrative of radicalism.